1999
DOI: 10.1046/j.1471-4159.1999.0732575.x
|View full text |Cite
|
Sign up to set email alerts
|

The Na‐G Ion Channel Is Transcribed from a Single Promoter Controlled by Distinct Neuron‐ and Schwann Cell‐Specific DNA Elements

Abstract: Na-G is a putative sodium (or cationic) channel expressed in neurons and glia of the PNS, in restricted neuronal subpopulations of the brain, and in several tissues outside the nervous system, like lung and adrenal medulla. To analyze the mechanisms underlying tissuespecific expression of this channel, we isolated the 5Ј region of the corresponding gene and show that Na-G mRNA transcription proceeds from a single promoter with multiple initiation sites. By transgenic mice studies, we demonstrate that 600 bp co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…This discrepancy may reflect the existence of strong inhibitory cues that operate in vivo but are lacking in our ex vivo experimental system. In line with this hypothesis are the results of our previous studies in transgenic mice (Poiraud et al, 1999), showing that the same Na‐G constructs are unable to drive the β‐galactosidase reporter expression in astroglia in situ.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This discrepancy may reflect the existence of strong inhibitory cues that operate in vivo but are lacking in our ex vivo experimental system. In line with this hypothesis are the results of our previous studies in transgenic mice (Poiraud et al, 1999), showing that the same Na‐G constructs are unable to drive the β‐galactosidase reporter expression in astroglia in situ.…”
Section: Discussionsupporting
confidence: 64%
“…In a recent work, we characterized the 5′ region of the Na‐G gene and have shown that, irrespective of their tissue or cell‐type origin, Na‐G mRNAs originate from a single promoter (the nucleotide sequence for the 11.7 kilobase Na‐G genomic fragment has been deposited in the Genbank database under accession number AF125160). By studies in transgenic mice, some of the genomic regions controlling the tissue and cell‐type specificity of Na‐G transcript expression were identified (Poiraud et al, 1999). In the present article, we provide further information on the cellular and transcriptional mechanisms that control the Na‐G gene expression in astrocytes and Schwann cells.…”
Section: Introductionmentioning
confidence: 99%
“…The mouse basal promoter of Na x sodium channel is 91% homologous to the rat Na x promoter sequence, although the TSSs are not at the same position (Poiraud et al, 1999). We found that NGFI-C and Ebox sites are conserved in both promoters, suggesting the possibility that these elements are also important for promoter activity in rat.…”
Section: Discussionmentioning
confidence: 73%
“…The GATA1 site, which has no significant contribution to promoter activity in mouse, is not conserved in rat. Poiraud et al (1999) suggested that a 600-bp fragment of the Na x rat promoter from position -375 nt to the end of exon 1, is sufficient to drive specific transcription in CNS neurons as much as PNS neurons in transgenic mice. Contrary to their proposal, the results derived from our functional analysis experiments using mouse Na x suggest that Na x basal promoter is active in all cells and that its tissue-specific expression is regulated by repression.…”
Section: Discussionmentioning
confidence: 99%
“…1998, 1999). Finally, the tissue specific gene promoter for the NAG channel (Poiraud et al. 1999) is somewhat similar to the Scn10a promoter.…”
Section: Discussionmentioning
confidence: 99%